Comparative Analysis of Engineering and Art Learner’s Readiness towards the use of E-Portfolio - Bahsan, Rosnadiah; Nor Azlan Mohamad, Syamsul; Nur Dini Mahazan, Siti (International Journal of Engineering and Technology, 2018)
This paper presents the comparative analysis learnersâ€™ readiness among Engineering and Art students in higher learning institution. The study was focused on examining 120 students from Engineering and Art cluster to practice e-Portfolio for their courses. The pilot study was tested the reliability coefficient with Cronbachâ€™s alpha (Î±) of 0.825. The survey of learner readiness was divided into five constructs to assess the readiness towards using e-portfolio for future assessment purposes. The finding was concluded that the students are indeed ready to use e-Portfolio as an appropriate platform for integrative learning. The use of e-Portfolio will broaden the possibility to promote outcome-based education and constructive alignment which encompassed practical skills such as critical thinking, problem solving, information management and lifelong skills. The preliminary study proved that e-Portfolio is beneficial to students, faculty and stakeholders.Â